Effect of surface treatment on the fatigue strength of additive manufactured Ti6Al4V alloy (Fracture and Structural Integrity, 2020)
Different alloys can be used for Additive Manufacturing (AM) with good structural strength. Among the titanium alloys, Ti6Al4V is the most used, especially for aerospace applications. There have been many analyses of the mechanical properties of additive manufactured Ti-6Al-4V with very good static strength results in general. However, there are still some difficulties to get fatigue properties close enough to the ones of specimens manufactured using traditional processesConsidering the high effect of surface roughness on the fatigue strength of  AM specimens, this work deals with the effect produced by some surface treatments on the fatigue properties. Five treatments have been used for comparison. All specimens were annealed previously to reduce residual stresses, as well as sand blasted to reduce the roughness. The treatments considered are: 1) no treatment after annealing and sand blasting; 2) shot peening; 3) shot peening plus Chemical Assisted Surface Enhancement (CASE); 4) laser shock peening, and 5) HIP. After fatigue testing, a comparison of the results has been carried out. It was found that laser peening produced the best results, followed by shot peening plus CASE and shot peening, with the lowest strength produced by HIP as well as just sand blasting after thermal treatment.
Keywords: Additive manufacturing; fatigue strength of AM elements; shot peening; laser shock peening; superfinishing; fatigue strength improvement